Sharia Banking Image in East Java Indonesia: Reviewed from Service Quality, Product Quality, and Customer Value - Panjaitan, Feliks Anggia Binsar Kristian (International Review of Management and Marketing, 2019)
The research objective was to find clarity about the effect of service quality, product quality, customer value and the image of Islamic banking in East Java. The research approach is quantitative, explanatory. The population of this study is Islamic banking customers in East Java. The research sample was 270 respondents and the sampling method used a purposive method. The analysis technique uses structural equation modeling with the warp PLS analysis tool. The results showed clarity that: Service quality affects customer value, and does not affect the banking image. Product quality has an effect on customer value and banking image. Customer value influences the banking image. Therefore, Islamic banking management should innovate and create services that are Islamic in nature and that are different from those of conventional banks. Keywords: Service Quality, Product Quality, Customer Value, Banking Image JEL Classifications: G21, L84, E23 DOI: https://doi.org/10.32479/irmm.8342